Novel highly sensitive protein sensors based on tapered optical fibres modified with Au-based nanocoatings - Urrutia, Aitor; Bojan, Kartheka; Marques, Leonel; Mullaney, Kevin; Goicoechea, Javier; James, Stephen; Clark, Matt; Korposh, Sergiy; Tatam, Ralph (Hindawi Publishing Corporation, 2016)
Novel protein sensors based on tapered optical fibres modified with Au coatings deposited using two different procedures are proposed. Au-based coatings are deposited onto a nonadiabatic tapered optical fibre using (i) a novel facile method composed of layer-by-layer deposition consisting of polycation (poly(allylamine hydrochloride), PAH) and negatively charged SiO₂ nanoparticles (NPs) followed by the deposition of the charged Au NPs and (ii) the sputtering technique.The Au NPs and Au thin film surfaces are then modified with biotin in order to bind streptavidin (SV) molecules and detect them. The sensing principle is based on the sensitivity of the transmission spectrum of the device to changes in the refractive index of the coatings induced by the SV binding to the biotin. Both sensors showed high sensitivity to SV, with the lowest measured concentration levels below 2.5 nM. The calculated binding constant for the biotin-SV pair was 2.2×10‾¹¹ M‾¹ when a tapered fibre modified with the LbL method was used, with a limit of detection (LoD) of 271 pM. The sensor formed using sputtering had a binding constant of 1.01 × 10‾¹⁰ M‾¹ with a LoD of 806 pM. These new structures and their simple fabrication technique could be used to develop other biosensors.